What we owe the future - MacAskill, William (New York Hachette Book Group, 2022)
One of the most stunning achievements of moral philosophy is something we take for granted: moral universalism, or the idea that every human has equal moral worth. In What We Owe the Future, Oxford philosopher William MacAskill demands that we go a step further, arguing that people not only have equal moral worth no matter where or how they live, but also no matter when they live. This idea has implications beyond the obvious (climate change) - including literally making sure that there are people in the future: It's not unusual to hear someone way, "Oh, I could never bring a child into this world." MacAskill argues that the sentiment itself may well be immoral: we have a responsibility not just to consider whether the world of the future will be suitable for supporting humans, but to act to make sure there are humans in it. And while it may seem that the destructive capacity of modern industrial technology means that we ought to eschew it as much as possible, MacAskill argues for optimism in our ability to (eventually) get technology right, for the future's benefit, and ours. Where Hans Rosling's Factfulness and Rutger Bregman's Utopia for Realists gave us reasons for hope and action in the present, What We Owe the Future is a compelling and accessible argument for why solving our problems demands that we worry about the future. And ultimately it provides an answer to the most important question we humans face: can we not just endure, but thrive?"
Includes bibliographical references and index.
Keywords: Altruism